A Security Architecture for Mobile Computing-Based IoT - Farina Mutia; Eugene Ario Suradilaga; Raymond Giovadius (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
The Internet of Things (IoT) is a complex technology with various applications that have become a vital part of our daily life. The number of connected devices and the Internet of Things continues to increase. In terms of bandwidth, service availability, security controls, cyberattacks, and privacy problems, transporting the huge data created by these IoT devices to the cloud offers concern and challenges comprising intermittent connection, service unavailability, data loss at rest, in use, and in motion, unhardened device and server, unpatched device and server, and exploitation vulnerabilities. Mobile computing (MC) is a strategic solution to tackle these difficulties by offering flexible data processing and storage to end users, increase security controls and with customized IoT devices for varied geographic locations. This paper provides a complete description of the components of the IoT architecture. After that, it elaborates on similar security threats and potential cyberattacks in the context of mobile computing-based IoT and suggests solutions. In conclusion, we provide a secure mobile computing architecture design for IoT applications.